The influence of career commitment on subjective career success in the context of media industry: mediating role of career resilience - Bhawna; Sanjeev Kumar Sharma; Mohd Asif Shah (Cogent Business & Management, 2024)
The present study explores the relationship between career commitment and subjective career success among media journalism industry employees. Additionally, it investigates the mediating role of career resilience behavior while anchoring its theoretical foundation in the career self-determination theory. The media journalism industry, characterized by burnout, demanding schedules and the mismatch of personal and professional commitments, provides a fitting context to examine the dynamics of career commitment and subjective career success. Using a structural equation modeling approach, the hypotheses were tested on 303 participants from the Punjab and Chandigarh regions in India. The results of the structural equation modeling affirmed the career commitment's substantial direct and indirect influence on subjective career success, mediated by the career resilience variable. The implications derived from this study are pertinent for the media journalism sector. It underscores the pivotal role of cultivating career-committed behavior among employees and advocating for strategic career development initiatives. This, in turn, fosters a resilient environment conducive to nurturing individual career accomplishments, transcending conventional benchmarks of organizational success. In conclusion, this research underscores the significance of transitioning from a traditional assessment of performance framework to a more subjective evaluation approach, ultimately contributing to cultivating a motivated and engaged workforce.
Keywords: 650; Subjective career success; career commitment; resilience; CSDT theory; media journalism industry